2022
DOI: 10.1021/acs.jpca.2c01052
|View full text |Cite
|
Sign up to set email alerts
|

Sensitization of Nd3+ Luminescence by Simultaneous Two-Photon Excitation through a Coordinating Polymethinic Antenna

Abstract: We have designed and synthesized two new cyaninic Nd3+ complexes where the lanthanide emission can be induced from simultaneous two-photon absorption followed by energy migration. These complexes correspond to a molecular design that uses an antenna ligand formed by the functionalization of a heptamethine dye with 5-ol-phenanthroline or 4-phenyl-terpyridine derivatives. These complexes employ the important nonlinear optical properties of symmetric polymethines to sensitize the lanthanide ion. We verified that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 120 publications
2
8
0
Order By: Relevance
“…This might suggest the operation of a L2 (dye) → Er energy transfer in the complex with a global rate constant = 7.7(2) × 10 8 s –1 and an efficiency of = 49(1)%. The latter interpretation corresponds to that previously proposed for rationalizing the titration of [(IR780-Phen)] + with Nd­(DBM) 3 in acetone, where = 2.5 × 10 9 s –1 and = 75% were reported for [(IR780-Phen)­Nd­(DBM) 3 ] + (Figure c) …”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…This might suggest the operation of a L2 (dye) → Er energy transfer in the complex with a global rate constant = 7.7(2) × 10 8 s –1 and an efficiency of = 49(1)%. The latter interpretation corresponds to that previously proposed for rationalizing the titration of [(IR780-Phen)] + with Nd­(DBM) 3 in acetone, where = 2.5 × 10 9 s –1 and = 75% were reported for [(IR780-Phen)­Nd­(DBM) 3 ] + (Figure c) …”
Section: Resultssupporting
confidence: 90%
“…This might suggest the operation of a L2(dye) → Er energy transfer in the complex with a global rate constant 2c). 85 However, as a control experiment, we additionally recorded the dye-centered π(S 1 ) emission lifetime in [L2Y(hfac) 3 ] + , and we found that it indeed closely mirrors that found for [L2Er(hfac) 3 ] + with τ π(S1) = 670(13) ps (Figure S27). One concludes that the shortening of the dye-centered emission lifetime in going from [L2] + to [L2Er(hfac) 3 ] + does not reflect the operation of the sensitizer to activator energy transfer as proposed in ref 85, but it is mainly due to the heavy atom effect and spin−orbit coupling (Z = 68 for erbium), which allow n o n -n e g l i g i b l e i n t e r s y s t e m c r o s s i n g w i t h…”
Section: Photophysical Properties Of Ligand [L2] + and Molecular Ligh...supporting
confidence: 61%
See 3 more Smart Citations